OPTIMIZATION OF BIOMIMETIC CRASH BOX STRUCTURE USING DESIGN FOR SIX SIGMA METHOD - Lucky Natalio, Anggi
As the global economy on the rise, the number of vehicles has seen a corresponding increase, leading to a rise in traffic accidents as well. In response, there is a need for advancements in transportation safety particularly concerning crashworthiness. Biomimetic principle has been applied in several studies and resulted in effective energy-absorbing structures. This research aims to analyze the optimization of the crashworthiness of a biomimetic crash box structure based on the tibia bone using the Design for Six Sigma (DFSS) methodology. Tibia is selected due to its primary load-bearing characteristic in compression, similar to that of a crash box. The methodology will include numerical simulation through LS DYNA and optimization via DFSS. The crash box structure designed consists of an outer structure shaped concavely, similar to the outer part of the tibia, and an inner re-entrant auxetic structure, similar to the inner part of the tibia. The model has a mean crushing force of 67.28 kN and a specific energy absorption (SEA) value of 7.89 kJ/kg. The optimization was conducted using DFSS with an ????18 orthogonal array and a signal-to-noise (S/N) ratio criterion of larger-the-better. The outcome of this optimization aimed for the highest SEA. Results indicate that the outer material of the crash box significantly contributes to the SEA. This optimization achieved a significant improvement, yielding an SEA of 9.64 kJ/kg gain and an S/N ratio of 3.27 dB gain. In conclusion, the optimized crash box has the mean SEA value of 17.51 kJ/kg, S/N ratio of 21.19 dB, and mean crushing force of 68.37 kN. This demonstrates that the biomimetic principle, inspired by the human tibia, can be applied in developing energy-absorbing structures to enhance transportation safety. Keywords: